On Some Volterra and Fredholm Problems via the Unified Integrodifferential Quadrature Method. (27th October 2011) - Zerarka, Abdelwahab; Soukeur, Abdesselam; Saidi, Hanane
Abstract : We present a new approach based on the formulation of the integrodifferential quadrature method (hereafter called IDQ) to handle Volterra's and Fredholm's equations. This approach is constructed and tested with some realistic numerical examples using the basic computational aspects.